Proverbs 28:20, 22 and Nigerian Youth’s Drive for Rapid Money - Uroko, Favour C. (2022)
While in the last decade the Nigerian youth quest for wealth has entered into the mainstream of Old Testament studies, Proverbs 28:20,22 have remained largely unexplored from this perspective. To address this omission, I intend to draw attention to the value of looking at the unbridled quest of Nigerian youth to get rich quickly through the lens of the pericope. Many investors fall prey to ponzi schemes, which are a type of investment scam. They are duped into believing that their money will return 100% in a short amount of time. Many ambitious investors have lost their money as a result of such schemes, which are unlawful and offer unrealistic profits. Proverbs 28:20,22 exist in a cultural context and communicate common values and beliefs in a community such as Nigeria. The rhetor encourages his audience to be faithful so that in the short and long run they will enjoy the needed blessings. This article explores the significance of using Proverbs 28:20,22 for interpreting youth participation in ponzi schemes. Furthermore, I demonstrated that greed and lack of patience are the remote causes of youth falling prey to ponzi schemes. The rhetoric analysis was used as the methodology due to the various rhetoric axioms that the rhetor employed in the pericope. It is believed that the pericope will speak anew to the youth quest for quick money.
Keywords: Greed; Old Testament; Ponzi schemes; Proverbs; Youth